Large Morgagni Hernia in an Adult Patient - Sofia Marques Santos; Eunice Oliveira; Nuno Ferreira Monteiro; Maria Manuela Soares; Alberto Mello e Silva (European Journal of Case Reports in Internal Medicine, 2015)
A 70-year-old woman presented to the emergency department with symptoms of a lower respiratory infection. A chest x-ray showed enlargement of the mediastinal space. The patient was admitted with a respiratory tract infection and started on antibiotic treatment. A computed tomography (CT) scan of the thorax revealed a large diaphragmatic hernia with stomach, large intestine and caudal pancreas lodged in the thoracic cavity. After the antibiotic treatment, the patient became asymptomatic and surgery repair was declined. Morgagni hernia is an uncommon type of congenital diaphragmatic hernia, which may be asymptomatic until late in life or may be present acutely with life threatening conditions.